FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA IPO DI BURSA EFEK INDONESIA (BEI) TAHUN 2018-2022 - Vanessa Fonda Sutjipto; Hendang Tanusdjaja (Fakultas Ekonomi Universitas Tarumanagara, 2024)
Share, and Company Size on Underpricing of Shares in Initial Public Offerings (IPO) with DER as a ModeratingVariable on the Indonesia Stock Exchange (BEI) 2018-2022. This type of research is quantitative research. The typeof data in this research is secondary data. The samples in this study were companies that experienced shareunderpricing during the Initial Public Offering (IPO) on the Indonesia Stock Exchange during 2018-2022. Thesampling technique uses purposive sampling. Data analysis in this research is multiple linear regression analysis,which is processed using SPSS version 26 software. The results obtained in this study indicate that AuditorReputation has a negative and significant effect on Stock Underpricing, Earning per Share has a negative andsignificant effect on Stock Underpricing, Company Size has a negative and significant effect on Stock Underpricing,DER is unable to moderate the influence of Auditor Reputation on Stock Underpricing, DER is unable to moderatethe influence of Earning per Share on Share Underpricing, and DER is unable to moderate the influence ofCompany Size on Share Underpricing.